Peran Social Media Marketing dan Brand Awareness Terhadap E-commerce Purchase Decision: Sebuah kajian Literatur - Hidayat, Syuhdan Ahmad; Vania, Amelindha (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study analyzes the impact of Social Media Marketing (SMM) and brand awareness on e-commerce purchase decisions. SMM has proven effective in enhancing brand visibility, building consumer relationships, and strengthening brand awareness, which in turn influences purchasing decisions. Brand awareness acts as a mediating variable that connects SMM to consumer purchase decisions. Factors such as Electronic Word of Mouth (E-WOM) and consumer engagement also play a significant role in enhancing the impact of SMM on purchasing decisions. The research employs a systematic literature review method by collecting articles with google scholar and publish or perish application, using keywords such as "Social Media Marketing," "Brand Awareness," and "E-commerce Purchase Decision." Data analysis is conducted descriptively to identify relevant trends and patterns. The findings provide insights for e-commerce companies to leverage social media in boosting brand awareness and influencing purchase decisions.